ANALYSIS OF THE DRAWING STAGES OF CHILDREN AGED 5-6 YEARS - Permatasari, Dinar Bulawan; Zulkarnaen, Zulkarnaen (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
This study aims to describe the stages of drawing work for children aged 5-6 years in the Bakti Ibu Begajah Playgroup, Sukoharjo District, Sukoharjo Regency. Based on the results of observations of children's drawing work put forward by Lowendfeld and Brittam, children aged 5-6 years are included in the pre-drawn period. Judging from the Observation instrument for the stages of drawing eight children aged 5-6 years, there is one child in the fifth stage, one child in the sixth stage, one child in the eighth stage and three children showing the ninth stage, one child in the tenth stage and the last one in the eleventh stage. Most of the children showed the results of the drawing in the nine stages of drawing observation. It was concluded that children's drawing results show different stages of the development of children's drawing with different characteristics and patterns of children aged 5-6 years because they are influenced by several factors such as interests, learning experiences, lifestyle and the environment around the child. By understanding the stages of drawing children, it can make it easier for educators to provide appropriate and directional stimulation to the next drawing stage.